Novel Anticancer Drug Protocols - Buolamwini, John K.; Adjei, Alex A.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2003)
With many potential molecular targets of anticancer agents already identified and many more yet to be discovered, the great challenges are now to successfully validate them, to devise relevant assays, and to translate the results into effective medicines for cancer patients. In Novel Anticancer Drug Protocols, expert basic researchers and clinicians from both industry and academia not only survey the whole arena of novel antitumor drug targets, but also present a wide-ranging selection of the key techniques currently being applied throughout anticancer drug discovery and development. Described in step-by-step detail to ensure successful results, these methods are employed in experiments involving such central topics as immunotherapy, angiogenesis, cancer metastasis, the cell cycle, signal transduction inhibitors, apoptosis, antibodies, antisense molecules, microarray gene expression analysis, flow cytometry, and PET imaging for cancer target validation. There are also proven methods for the preclinical identification of drug targets and for target validation during the clinical trials of novel agents. Each method provides background information, easy-to-follow instructions, notes on avoiding pitfalls, and alternative procedures. Eminently practical and user-friendly, Novel Anticancer Drug Protocols offers all researchers involved in cancer drug development a blend of the critical preclinical and clinical assays needed for the target validation and discovery of novel agents today.
Overview of Novel Anticancer Drug Targets -- Kinase Inhibitor Discovery Protocols -- Biomarker Assays for Phosphorylated MAP Kinase -- Assays for Cyclin-Dependent Kinase Inhibitors -- Identifying Inhibitors of ATM and ATR Kinase Activities -- Angiogenesis and Metastasis Protocols -- The Rat Aortic Ring Assay for In Vitro Study of Angiogenesis -- Real Time In Vivo Quantitation of Tumor Angiogenesis -- Use of Tumor-Activated Hepatic Stellate Cell as a Target for the Preclinical Testing of Anti-Angiogenic Drugs Against Hepatic Tumor Development -- Cell Motility, Adhesion, Homing, and Migration Assays in the Studies of Tyrosine Kinases -- Inflammatory Response of Tumor-Activated Hepatic Sinusoidal Endothelium as a Target for the Screening of Metastasis Chemopreventive Drugs -- Binding Assay for Selectins -- Determination of Peak Serum Levels and Immune Response to the Humanized Anti-Ganglioside Antibody-Interleukin-2 Immunocytokine -- Immunohistochemical Assays in the Clinical Setting -- Immunohistochemical Determination of EGFR-Tyrosine Kinase Inhibition in Clinical Samples -- Immunohistochemical Assays of Farnesyltransferase Inhibition in Patient Samples -- Protein Chaperoning/Degradation Protocols -- Assays for HSP90 and Inhibitors -- Assays for Proteasome Inhibition -- Protein-Protein and Protein-DNA Interactions -- The Mammalian Two-Hybrid Assay for Detection of Coactivator-Nuclear Receptor Interactions -- Preparation of DNA-Protein Complexes Suitable for Spectroscopic Analysis -- Antisense -- Antisense Oligonucleotide Inhibitors of MDM2 Oncogene Expression -- Genomics -- Pharmacogenetic Analysis of Clinically Relevant Genetic Polymorphisms -- Gene Expression Microarrays -- Methods for Isolation and Genetic Analysis of Circulating Tumor DNA in Patient Plasma -- Cell Lifespan/Longevity -- The Use of Early Sea Urchin Embryos in Anticancer Drug Testing -- In Vivo Imaging -- PET Screening of Anticancer Drugs -- Miscellaneous Protocols -- Assays for In Vitro and In Vivo Synergy -- Flow Cytometric Methods for Detection and Quantification of Apoptosis -- Assays for Neoplastic Cell Enrichment in Bone Marrow Samples.
Keywords: Pharmacy; Pharmacy